2007
DOI: 10.1007/s00534-007-1225-6
|View full text |Cite
|
Sign up to set email alerts
|

Do we need histology for a normal-looking gallbladder?

Abstract: A selective policy rather than routine histological examination of nonfibrotic or thickened-wall gallbladder has to be considered. This will reduce the burden on pathology departments, with significant cost savings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
64
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 21 publications
4
64
1
Order By: Relevance
“…In present study, lesions of gall bladder were more common in females than in males with a male to female ratio of 1:3.91 which was similar to other study carried out by Rahul et al [4], Asuquo et al [5], Tantia et al [6] and John et al [7], reported male to female ratio of 1:4.8; 1:5, 1:2.8 and 1:4 respectively. Most of the patients presented with pain upper abdomen, nausea and/or vomiting, which is consistent with findings by Laghari et al [8]. The most common histopathological finding in our study was chronic cholecystitis : 679(75.6%) specimens were reported as chronic inflammation with mucosal ulceration, denudation and wall infiltration by chronic inflammatory cells like neutrophils, macrophages, plasma cells and varying degree of fibrosis.…”
Section: Discussionsupporting
confidence: 91%
“…In present study, lesions of gall bladder were more common in females than in males with a male to female ratio of 1:3.91 which was similar to other study carried out by Rahul et al [4], Asuquo et al [5], Tantia et al [6] and John et al [7], reported male to female ratio of 1:4.8; 1:5, 1:2.8 and 1:4 respectively. Most of the patients presented with pain upper abdomen, nausea and/or vomiting, which is consistent with findings by Laghari et al [8]. The most common histopathological finding in our study was chronic cholecystitis : 679(75.6%) specimens were reported as chronic inflammation with mucosal ulceration, denudation and wall infiltration by chronic inflammatory cells like neutrophils, macrophages, plasma cells and varying degree of fibrosis.…”
Section: Discussionsupporting
confidence: 91%
“…However, a thickened wall is not specific to malignant transformation as it is also seen in an acutely inflamed gallbladder or chronic cholecystitis. Many studies differ on their definition of a thickened wall with 3 mm or even no clearly defined cutoff point [5,6]. However, in our institution the correlation of thickness of gallbladder wall with gallbladder cancer is not taken into consideration.…”
Section: Discussionmentioning
confidence: 98%
“…A small number of literature data studied the benefits of histopathologic examination of these two common surgical specimens [2][3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…N. T. Damor et al (14) and Khanna et al (19) reported that majority of non-neoplastic lesions of Gallbladder occurred in 3rd to 5th decades. While Bazoua et al (20) studied that neoplastic lesions developed in patients of age more than 50 yrs and maximum in age group 50 to 70 years. In the present study lesions of gallbladder were most common in the 4th and 5th decades.…”
Section: Discussionmentioning
confidence: 99%